Characterization and identification of congo red decolorizing bacteria from monocultures and consortia - Buan, Aileen J. (Aileen C. Jalandoni-Buan)
Congo red is a carcinogenic direct diazo dye used for the coloration of paper products. It is recalcitrant and is thus found in effluents of paper factories. Bacteria in consortia and monocultures capable of decolorizing Congo red were isolated previously. The consortia were initially labeled as IRRI-1 and S22. The monocultures were initially labeled as SB13B and SB12D. Members of the consortia were isolated and those capable of decolorizing Congo red were selected. IRRI-1C was the decolorizing member of the fermentative consortium IRRI-1 and S22B was the decolorizing member of the denitrifying consortium S22. IRRI-1C and S22B together with the consortia and monocultures isolated previously were characterized and identified. The decolorizing activity of IRRI-1C was found to be 92% while that of S22B was 96%. S22B and SB13B were able to degrade Congo red while reducing nitrate to nitrogen gas and nitrite. SB13B was identified as Escherichia coli by API 20 E, fatty acid analysis and 16S rRNA sequencing. SB12D was identified as Enterobacter cloacae by API 20 E, Escherichia coli by fatty acid analysis and as Enterobacter dissolvens by 16S rRNA sequencing. BIOLOG and 16S rRNA sequencing identified S22B as Pseudomonas citronellolis and Pseudomonas aeruginosa by fatty acid analysis. IRRI-1C was identified as Klebsiella oxytoca using API 20 E. Other than Congo red, the consortia were able to decolorize direct black and direct violet, while the monocultures except for SB13B were able to decolorize direct violet. The rate of decolorization by the consortia was faster than the monocultures isolated from them. Dye degradation occurred in the supernatant of sonicated cells, indicating that the dye degrading enzyme was located intracellularly. The monocultures and consortia were able to decolorize Congo red in polluted water while no decolorization of the dye was observed in clean water. The resident microorganisms together with other organic matter in the polluted water could have favored dye degradation.